2000
DOI: 10.1093/deafed/5.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind: Deaf and Hearing Children's Comprehension of Picture Stories and Judgments of Social Situations

Abstract: We compared 20 prelingually profoundly deaf adolescents (age: 11-16 years) and 20 matched, hearing adolescents on a picture-sequencing task and on a social judgment test. In addition, we also tested 14 younger deaf children (age: 6-10 years) and compared their data with those from 20 hearing peers as well as those from the older deaf participants on the picture-sequencing task. The results from this study did not provide evidence for the hypothesis that deaf adolescents possess significantly poorer knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The consensus of these studies is that the relatively poor performance of deaf individuals does not result from the experience of being deaf itself, but from the consequent delay in language exposure (Peterson and Siegal, 1999; Rhys-Jones and Ellis, 2000; Woolfe et al, 2002; Courtin and Melot, 2005; Moeller and Schick, 2006; Morgan and Kegl, 2006; Schick et al, 2007; Meristo et al, 2012, among others). What these studies have shown is that ToM abilities are delayed commensurate with the degree of delay of exposure to sign language.…”
Section: Study 4: Experiential False Beliefmentioning
confidence: 99%
“…The consensus of these studies is that the relatively poor performance of deaf individuals does not result from the experience of being deaf itself, but from the consequent delay in language exposure (Peterson and Siegal, 1999; Rhys-Jones and Ellis, 2000; Woolfe et al, 2002; Courtin and Melot, 2005; Moeller and Schick, 2006; Morgan and Kegl, 2006; Schick et al, 2007; Meristo et al, 2012, among others). What these studies have shown is that ToM abilities are delayed commensurate with the degree of delay of exposure to sign language.…”
Section: Study 4: Experiential False Beliefmentioning
confidence: 99%
“…Although deaf children appear to catch up later, early delays create significant problems for deaf children socially and emotionally. 81,82 Abusive experiences Surveys of adults in Norway and North America suggest that deaf children are between two and three times more likely to be sexually abused than hearing children, and less likely to disclose their abuse. 83 These experiences may lead to subsequent substance misuse behaviours and negative mental health outcomes, 84 and abuse is in general associated with higher rates of negative mental health outcomes.…”
Section: Emotional Development and Theory Of Mindmentioning
confidence: 99%
“…Borgna et al (2011) suggested this as an example of the "unskilled and unaware effect" (Kruger & Dunning, 1999), wherein having lesser ability in a domain leaves one less able to recognize that fact. Indeed, a central aspect of social maturity is the ability to appreciate social situations from the points of view of others, a domain in which deaf children and adolescents have been found to have difficulty (e.g., Peterson, Slaughter, Moore, & Wellman, 2016;Punch & Hyde, 2011;Rhys-Jones & Ellis, 2000;Rieffe, Netten, & Broekhof, 2015;Terwogt & Rieffe, 2004). Caldarella and Merrell (1997) found self-management, including social maturity, self-control/social convention, and respect for social rules to be one of the most common dimensions to emerge from meta-analyses of studies examining social skills of (hearing) children and adolescents (see Doren et al, 2012).…”
mentioning
confidence: 99%